Artemis awakening - Lindskold, Jane M. (Tor, 2014)
"The distant world Artemis is a pleasure planet created out of bare rock by a technologically advanced human empire that provided its richest citizens with a veritable Eden to play in. All tech was concealed and the animals (and the humans brought to live there) were bioengineered to help the guests enjoy their stay. But the Empire was shattered in a horrific war; centuries later humanity has lost much of their advanced technology, and Artemis is a fable told to children. Until young archeologist Griffin Dane finds intriguing hints that send him on a quest to find the lost world. Stranded on Artemis after crashing his ship, he encounters the Huntress Adara and her psych-linked companion, the puma Sand Shadow. Their journey with her will lead Dane to discover the planet's secrets...and perhaps provide a key to give unimagined power back to mankind" --